Research Trends in Risk Communication for Earthquake Disaster Preparedness - Elmina Furi; Fatmah Fatmah; Evi Frimawaty (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2026)
Earthquakes are among the most destructive natural hazards, with significant impacts on social, economic, environmental, and infrastructural systems. In this context, risk communication plays a strategic role as an instrument for conveying information about hazards, potential consequences, and mitigation measures to communities and stakeholders. Despite the growing body of research in disaster risk communication, existing studies remain largely fragmented and tend to focus on specific local contexts or particular empirical approaches. This study aims to map and analyze the development of research on risk communication in the context of earthquake preparedness using a bibliometric approach based on scientific publications indexed in Scopus during the period 2016–2025. The method employed is bibliometric analysis following the PRISMA protocol to ensure a systematic and transparent data selection process. Data were analyzed using VOSviewer and Biblioshiny to generate network visualizations, keyword clusters, and thematic evolution. The novelty of this study lies in its comprehensive, data-driven mapping of the intellectual structure and research dynamics of risk communication in earthquake preparedness, an area that remains relatively underexplored. The findings are expected to provide a more holistic understanding of research trends, identify existing gaps, and serve as a basis for developing more effective and evidence-based risk communication strategies to enhance community preparedness and resilience to earthquake disasters.